Epidemiology, risk factors, and pathogenesis associated with a superbug: A comprehensive literature review on hepatitis C virus infection. (June 2022) - Tariq, Mehlayl; Shoukat, Abu Bakar; Akbar, Sedrah; Hameed, Samaia; Naqvi, Muniba Zainab; Azher, Ayesha; Saad, Muhammad; Rizwan, Muhammad; Nadeem, Muhammad; Javed, Anum; Ali, Asad; Aziz, Shahid
Viral hepatitis is a major public health concern. It is associated with life threatening conditions including liver cirrhosis and hepatocellular carcinoma. Hepatitis C virus infects around 71 million people annually, resultantly 700, 000 deaths worldwide. Extrahepatic associated chronic hepatitis C virus accounts for one fourth of total healthcare load. This review included a total of 150 studies that revealed almost 19 million people are infected with hepatitis C virus and 240, 000 new cases are being reported each year. This trend is continually rising in developing countries like Pakistan where intravenous drug abuse, street barbers, unsafe blood transfusions, use of unsterilized surgical instruments and recycled syringes plays a major role in virus transmission. Almost 123–180 million people are found to be hepatitis C virus infected or carrier that accounts for 2%–3% of world's population. The general symptoms of hepatitis C virus infection include fatigue, jaundice, dark urine, anorexia, fever malaise, nausea and constipation varying on severity and chronicity of infection. More than 90% of hepatitis C virus infected patients are treated with direct-acting antiviral agents that prevent progression of liver disease, decreasing the elevation of hepatocellular carcinoma. Standardizing the healthcare techniques, minimizing the street practices, and screening for viral hepatitis on mass levels for early diagnosis and prompt treatment may help in decreasing the burden on already fragmented healthcare system. However, more advanced studies on larger populations focusing on mode of transmission and treatment protocols are warranted to understand and minimize the overall infection and death stigma among masses.